The Impact of Business and Political News on the GCC Stock Markets - Alanoud Al-Maadid; Guglielmo Maria Caporale; Fabio Spagnolo; Nicola Spagnolo (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper investigates the impact of business and political news on stock market returns in the Gulf Cooperation Council (GCC) countries. For this purpose, it employs a Markov switching model including a separate index for each of the two categories of news considered. The results indicate the importance of news as drivers of GCC stock returns, with business news playing a more substantial role; further, news released in the largest financial markets in the regions are found to have significant cross-border effects.
Keywords: C32; F36; G15; 330; business news; GCC countries; Markov switching model; political news